Routine screening for Chlamydia trachomatis and Neisseria gonorrhoeae in first trimester abortion - Ryan Schlueter; Andrea Siu; James Shelton; Men-Jean Lee (Elsevier, 2018)
Currently no recommendation exists to collect genital culture for Chlamydia trachomatis and Neisseria gonorrhoeae at diagnosis of spontaneous abortion. A retrospective cross sectional study was performed to identify first trimester abortions with concurrent genital culture collection in an emergency room setting. The results were compared to most current 2015 Center for Disease Control (CDC) statistics. Among women aged 15-24 the rate of C. trachomatis was increased to 20.0% and greater than CDC rate of 6.7% (RR 2.97, p < 0.0001). No positive screens for C. trachomatis were found above age 30 and the study rate of N. gonorrhoeae was not significantly elevated. Younger women presenting for miscarriage have high prevalence of C. trachomatis in comparison to 2015 CDC statistics. Routine genital culture could be recommended at diagnosis of first trimester spontaneous abortion. Keywords: Abortion, Incomplete, Spontaneous, Chlamydia trachomatis, Neisseria gonorrhoeae, Reproductive health